Radiological features of gait phenotypes in patients with idiopathic normal pressure hydrocephalus - Silvia Nicolosi; Silvia Nicolosi; Massimiliano Todisco; Massimiliano Todisco; Matteo Paoletti; Eduardo Caverzasi; Eduardo Caverzasi; Francesco Tarantino; Elena Ballante; Francesca Valentino; Roberta Zangaglia; Silvia Figini; et al. (Frontiers in Aging Neuroscience)
IntroductionAccording to the higher-level gait disorder (HLGD) pattern, patients with idiopathic normal pressure hydrocephalus (iNPH) can be divided into two motor phenotypes; a disequilibrium (wide-based gait) subtype and a parkinsonian (locomotor) subtype. We aimed to understand the neuroimaging correlates of iNPH phenotyping into different gait patterns, by assessing specific radiological features and their correlations with clinical scores.MethodsWe enrolled 86 probable iNPH patients (53 males; age range: 69–88 years), who underwent a comprehensive clinical assessment, including neuropsychological tests, and a conventional MRI scan. The cohort was subdivided into disequilibrium subtype (29 subjects) and parkinsonian subtype of HLGD (57 patients) based on gait evaluation. We compared the iNPH subtypes assessing differences in eight linear radiological indexes and their clinical correlates.ResultsThe Height of the third ventricle was the only radiological feature that differed between the two motor phenotypes (p < 0.05), being higher in the parkinsonian subtype and showing a trend of correlation with the motor score of the Movement Disorder Society-Unified Parkinson’s Disease Rating Scale and with the continence score of the iNPH Rating Scale. Among several clinical-radiological correlations, a reduced callosal angle correlated with the severity of motor and urinary symptoms (p < 0.05).DiscussionA greater height of the third ventricle possibly leading to a top-down compressive effect on the midbrain could be a neuroimaging marker of the parkinsonian phenotype of iNPH. The extensive correlations between linear radiological indices and clinical scales suggest a potential role for radiological features in clinical monitoring.